2019
DOI: 10.1590/0102-311x00174818
|View full text |Cite
|
Sign up to set email alerts
|

Women economic empowerment via cash transfer and microcredit programs is enough to decrease intimate partner violence? Evidence from a systematic review

Abstract: Intimate partner violence (IPV) is a worldwide public health problem. Many proposals aiming to eliminate its occurrence include the empowerment of women through their socio-economic development. In this context, some studies suggested that microcredit programs (MP) and cash transfer programs (CTP) are initiatives that can also reduce the risk of IPV. Others pointed to an opposite effect. The objective of this study was to investigate the influence of women’s economic empowerment in MP and CTP on the risk of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…This is consistent with study findings in Bangladesh [53] and Peru [54]. This might be due to the reason that women who are empowered are able to fight for their rights and will not accept men to fully dictate to them which could result in sexual, physical or emotional violence [55]. Besides, in Ethiopia, majority of the cultures considered women to be subordinated or controlled by men and therefore, women in community with high women empowerment are not depend men for their lives and tend to resist some of the decisions of men which may bring about intimate partner violence [56].…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with study findings in Bangladesh [53] and Peru [54]. This might be due to the reason that women who are empowered are able to fight for their rights and will not accept men to fully dictate to them which could result in sexual, physical or emotional violence [55]. Besides, in Ethiopia, majority of the cultures considered women to be subordinated or controlled by men and therefore, women in community with high women empowerment are not depend men for their lives and tend to resist some of the decisions of men which may bring about intimate partner violence [56].…”
Section: Discussionsupporting
confidence: 91%
“…Women’s financial independence can be addressed by economic interventions, particularly those that include social components that engage men around gender norms and equity. This can increase women’s social capital and empowerment and lead to a reduction in IPV risk and improved mental and physical health outcomes [ 23 , 32 , 53 55 , 58 ]. However, interventions that increase a woman’s economic empowerment or independence, particularly when not combined with social intervention components to address elements such as safety planning, can increase the risk of violence in the home [ 13 , 30 , 32 , 49 , 53 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Still, empirical evidence on CTP and IPV in Latin American countries is controversial. In the most recent systematic review on the subject, T. H. Leite et al (2019) showed that some CTPs reduce and others show no influence on the prevalence of physical and psychological violence against women.…”
Section: Introductionmentioning
confidence: 99%
“…Still, empirical evidence on CTP and IPV in Latin American countries is controversial. In the most recent systematic review on the subject, T. H. Leite et al (2019) showed that some CTPs reduce and others show no influence on the prevalence of physical and psychological violence against women. However, the authors pointed out that there is considerable heterogeneity in the results according to cultural norms, regarding gender roles, socioeconomic contexts, family dynamics, and individual characteristics (T. H. Leite et al, 2019).…”
Section: Introductionmentioning
confidence: 99%